Enhancing dissolving pulp quality of mixed raw materials through pre-hydrolysis kraft-cooking: A study on Acacia crassicarpa and Terminalia catappa - Sahan, Yusnimar; Rahmi, Sri Wahdini; Evelyn; Herman, Syamsu; Chairul; Khairat; Ohi, Hiroshi; Amri, Amun (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Acacia crassicarpa wood is widely used in Indonesia as a raw material for dissolving pulp (DP) by the kraft-cooking process. Given that Indonesia has a rich variety and abundance of cellulose-rich wood, it is deemed crucial to research alternative raw materials, such as Terminalia catappa wood. As an alternative source of raw material, Terminalia catappa possesses excellent adaptability to various environmental conditions and is easy to grow everywhere. The current research sought to produce DP using the mixtures of materials from these two plant species as raw materials by pre-hydrolysis, kraft-cooking, and Elementary Chlorine Free (ECF) bleaching. The DP produced had ISO brightness > 88%, alpha-cellulose content > 94%, viscosity > 6.2 cP, and pentosan content of 2.54%. The DP quality traits have met the SNI 938:2017 standards for rayon-grade pulp. Acacia Crassicarpa and Terminalia Catappa are the prospective wood mixture for producing high-quality dissolving pulp via the kraft-cooking process.